2019
DOI: 10.1007/s10654-019-00558-7
|View full text |Cite
|
Sign up to set email alerts
|

Validation of multiple sclerosis diagnoses in the Swedish National Patient Register

Abstract: Population-based registers are widely used in epidemiological studies. We aimed to estimate the validity of multiple sclerosis (MS) diagnoses registered in the Swedish National Patient Register (NPR) by two sequential register-based case-definition algorithms. Prevalent MS patients aged 16-64 years were identified from the in-and specialised out-patient NPR in 2001-2013, using International Classification of Diseases code G35. These identified MS diagnoses were validated through two sequential register-based c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…It has fewer diagnostic errors among younger patients and a high level of accuracy for MS diagnoses. 33 A recent study confirmed 92.5% of all MS diagnosis in the NPR 34 and previous validation studies have reported more than 99% of all somatic hospital discharges are registered in the register and 85-95% of all inpatient diagnoses are valid. 33 In our study we used two MS diagnoses separated by at least six months which notably increased the accuracy.…”
Section: Discussionmentioning
confidence: 76%
“…It has fewer diagnostic errors among younger patients and a high level of accuracy for MS diagnoses. 33 A recent study confirmed 92.5% of all MS diagnosis in the NPR 34 and previous validation studies have reported more than 99% of all somatic hospital discharges are registered in the register and 85-95% of all inpatient diagnoses are valid. 33 In our study we used two MS diagnoses separated by at least six months which notably increased the accuracy.…”
Section: Discussionmentioning
confidence: 76%
“…A patient with a first-ever hospital visit concerning amyotrophic lateral sclerosis, multiple sclerosis or Parkinson’s disease was defined as an incident case, and the date of the first hospital visit was defined as the date of diagnosis. Such definitions of amyotrophic lateral sclerosis, multiple sclerosis and Parkinson’s disease have been estimated previously, with a positive predictive value of 91% for amyotrophic lateral sclerosis (in Stockholm during 2013–2014) ( Mariosa et al , 2017 ), 92.5% for multiple sclerosis (in Sweden during 2001–2013) ( Murley et al , 2019 ) and 70.8% for Parkinson’s disease (in Sweden during 1964–2009 based on inpatient care alone) ( Feldman et al , 2012 ). For each case, we then randomly selected five controls who were individually matched to the case by age, sex and county of residence, using the method of incidence density sampling.…”
Section: Methodsmentioning
confidence: 75%
“…A limitation of the study is the lack of validation for patients with concurrent ALS and autoimmune disease, because of the historical and nationwide nature of data. However, the validity of ALS diagnosis ( 16) and many autoimmune diseases, including multiple sclerosis (36), rheumatoid arthritis (37), Guillain-Barr e syndrome (38), diabetes (39), psoriasis (40), ulcerative colitis and Crohn's disease (41), polymyalgia rheumatica (42), ankylosing spondylitis (43), celiac disease (44), Wegener's granulomatosis (45), Sarcoidosis (46), Addison's disease (47), pemphigoid (48), is known to be satisfactory in the Swedish Patient Register. The similar results noted in the sensitivity analyses where we used more strict definitions of autoimmune diseases also alleviated the concern to some extent.…”
Section: Discussionmentioning
confidence: 99%